Religion and popular culture in America - Forbes, Bruce David; Mahan, Jeffrey H. (University of California Press, 2017)
The connection between popular culture and religion is an enduring part of American life. With seventy-five percent new content, the third edition of this multifaceted and popular collection has been revised and updated throughout to provide greater religious diversity in its topics and address critical developments in the study of religion and popular culture. Ideal for classroom use, this expanded volumegives increased attention to the implications of digital culture and the increasingly interactive quality of popular cultureprovides a framework to help students understand and appreciate the work in diverse fields, methods, and perspectivescontains an updated introduction, discussion questions, and other instructional tools